(untitled) (Tempo e Argumento, 2022)
This article aims to discuss the emergence of the struggle for better living conditions in the periphery of Rio de Janeiro, in the context of the reappearance of movements and organizations of popular origin demanding the enjoyment of the right to citizenship in the country’s political scene. Choosing as its privileged source the Jornal da Baixada, journalistic organ of the so-called “alternative press” published in the municipality of São João de Meriti-RJ in the passage between the 1970s and 1980s, we propose to analyze the construction of a narrative that intentionally assumed the political objective of building an identity perception about the Baixada Fluminense distanced from the stereotype that this is a region traditionally associated with violence, the lack of public services and clientelist political practices. Without denying the daily difficulties experienced by its citizens, Jornal da Baixada sought to produce a strongly politicized discourse in which the capacity of mobilization and organized resistance of the population of Baixada Fluminense to the authorities and powers constituted during the period of legitimacy crisis that characterized the last years of the civil-military dictatorship implanted after 1964.